PENGARUH KEPEMILIKAN INSTITUSIONAL, UMUR PERUSAHAAN, DAN KARAKTERISTIK EKSEKUTIF DAN TERHADAP TAX AVOIDANCE - rispandy, arina; Mubarak, Abdullah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
ABSTRACK. This study aims to analyze the effect of institutional ownership, company age, and executive characteristics on tax avoidance. This research was conducted by analyzing the financial statements of companies in the Consumer Non-Cyclical sector listed on the Indonesia Stock Exchange (IDX) during the period 2019-2024. The sample used in this study consisted of 32 companies in the Consumer Non-Cyclical sector using purposive sampling technique. The data used in this study is secondary data in the form of financial reports from each company that has been sampled for research. The variables used in this study are Institutional Ownership (X1) as the first independent variable, Company Age (X2) as the second independent variable, and Executive Characteristics (X3) as the third independent variable, and Tax Avoidance (Y) as the dependent variable. The panel data regression method was used as the research method in this study. The analysis of the research results used the Eviews 12 software. The results of the study show that the selected model is the Fixed Effect Model (FEM). The results of this study indicate that Institutional Ownership partially has no effect on tax avoidance, while Company Age and Executive Characteristics partially have a negative effect on tax avoidance. Simultaneously, Institutional Ownership, Company Age, and Executive Characteristics affect tax avoidance. Keywords: Institutional Ownership, Company Age, Executive Characteristics, Tax Avoidance.